Impact of adjuvant: Trivalent vaccine with quadrivalent-like protection against heterologous Yamagata-lineage influenza B virus - Myers, Mallory L.; Gallagher, John R.; Woolfork, De’Marcus D.; Stradtmann-Carvalho, Regan K.; Maldonado-Puga, Samantha; Bock, Kevin W.; Boyoglu-Barnum, Seyhan; Syeda, Hubza; Creanga, Adrian; Alves, Derron A.; Kanekiyo, Masaru; Harris, Audray K. (Frontiers in Immunology, 2022)
As new vaccine technologies and platforms, such as nanoparticles and novel adjuvants, are developed to aid in the establishment of a universal influenza vaccine, studying traditional influenza split/subunit vaccines should not be overlooked. Commercially available vaccines are typically studied in terms of influenza A H1 and H3 viruses but influenza B viruses need to be examined as well. Thus, there is a need to both understand the limitations of split/subunit vaccines and develop strategies to overcome those limitations, particularly their ability to elicit cross-reactive antibodies to the co-circulating Victoria (B-V) and Yamagata (B-Y) lineages of human influenza B viruses. In this study, we compared three commercial influenza hemagglutinin (HA) split/subunit vaccines, one quadrivalent (H1, H3, B-V, B-Y HAs) and two trivalent (H1, H3, B-V HAs), to characterize potential differences in their antibody responses and protection against a B-Y challenge. We found that the trivalent adjuvanted vaccine Fluad, formulated without B-Y HA, was able to produce antibodies to B-Y (cross-lineage) on a similar level to those elicited from a quadrivalent vaccine (Flucelvax) containing both B-V and B-Y HAs. Interestingly, Fluad protected mice from a lethal cross-lineage B-Y viral challenge, while another trivalent vaccine, Fluzone HD, failed to elicit antibodies or full protection following challenge. Fluad immunization also diminished viral burden in the lungs compared to Fluzone and saline groups. The success of a trivalent vaccine to provide protection from a cross-lineage influenza B challenge, similar to a quadrivalent vaccine, suggests that further analysis of different split/subunit vaccine formulations could identify mechanisms for vaccines to target antigenically different viruses. Understanding how to increase the breadth of the immune response following immunization will be needed for universal influenza vaccine development.